Analysis of the Effect of Production on Investment in Digging - Loading and Transport Equipment PT. Y in Block 8 of PT X Limestone Mining, South Sulawesi Province - Muhammad Fikra Irwan; Tri Gamela Saldy (Departemen Teknik Pertambangan FT UNP, 2024)
In cement production, raw materials are needed which consist of primary raw materials, namely limestone with a percentage of 85%, and clay with a percentage of 13%, apart from that, secondary raw materials are also needed as correction materials which come from tuff, silica and gypsum with a total percentage. namely 2%. The large demand for limestone requires PT X to carry out its own mining with the assistance of contractors. One of the contractors carrying out this mining is PT Y in block 8. Mining carried out by PT Y in block eight has a target of 74,000 tons in October. From observations in the field, there was an obstacle, namely the incompatibility of equipment which affected production achievements in October. From the analysis that has been carried out, a match factor of 1.275 was obtained so that the means of transport were reduced from 6 means of transport to 5 means of transport. From productivity calculations, the results obtained are that if you use 1 digging tool and 6 transport tools, the production that can be done in one day is 2,823.08 tons, whereas if you use 5 transport tools, the production that can be produced in one day is 2,900.704 tons. The total cost of ownership and operational costs if using 1 digging and loading equipment and 6 transportation equipment per year is IDR 4,580,431,703.68. Meanwhile, if you use 1 digging and loading equipment and 5 transportation equipment, the total annual ownership and operational costs that must be incurred are IDR 4,246,980,096.24. Using 1 dig-loading tool and 5 transport tools is much more profitable than using 1 dig-loading tool and 6 transport tools.